Analisa Pendapatan Usaha Daging Sapi di Pasar Bawah Takengon Kabupaten Aceh Tengah - Firmansyah Firmansyah; Azhari Azhari; Ira Zulfa (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
The problem so far is that there is no determination of how much beef business income, especially in the lower market of Takengon, so to find out the amount of beef business income in the Lower market of Takengon, an analysis of income measured in economic terms is made. The data collection method used is a field study technique, which is research conducted directly on the object by interviewing beef sellers, especially in the lower market area of Takengon which will be analyzed by quantitative methods by comparing field data based on ratio calculations using the income formula. The results showed that the total costs incurred for the beef business within one year reached Rp. 274,700,000 with an average of Rp. 22,891,700 while the amount of production in the beef business within one year reached Rp. 447,600,000 in one year with an average receipt of Rp. 37,300,000 and the net profit received within one year was Rp. 65,300,000 with an average profit per month of Rp. 5,441,000.